2011
DOI: 10.1002/adsc.201000858
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3‐Arylindole‐2‐carboxylates via Copper‐Catalyzed Hydroarylation of o‐Nitrophenyl‐Substituted Alkynoates and Subsequent Cadogan Cyclization

Abstract: A two-step route to biologically important 3-arylindole-2-carboxylic esters has been successfully established: o-nitrophenyl-substituted alkynA C H T U N G T R E N N U N G oates underwent copper-catalyzed hydroarylation in the presence of commercially available arylboronic acids to afford 3,3-diarylacrylates, which were then converted to indolecarboxylates via a modified Cadogan cyclization using a molybdenum catalyst and triphenylphosphine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Cadogan cyclization is known to be a powerful method for transforming nitroaromatic compounds into various types of nitrogen heterocycles. 43 44 The first step was the copper-catalyzed conjugate arylation of 94, which proceeded in MeOH at 28 1C to furnish 95 in 65-79% yields. The second Cadogan cyclization was performed using a molybdenum-catalyzed protocol to give generally high yields of 96.…”
Section: Heterocycle Synthesis Via Palladiumcatalyzed Reductive Heck ...mentioning
confidence: 99%
“…Cadogan cyclization is known to be a powerful method for transforming nitroaromatic compounds into various types of nitrogen heterocycles. 43 44 The first step was the copper-catalyzed conjugate arylation of 94, which proceeded in MeOH at 28 1C to furnish 95 in 65-79% yields. The second Cadogan cyclization was performed using a molybdenum-catalyzed protocol to give generally high yields of 96.…”
Section: Heterocycle Synthesis Via Palladiumcatalyzed Reductive Heck ...mentioning
confidence: 99%
“…Although these two methods produce mutually opposite stereoisomers, subsequent Cadogan cyclization is expected to afford the desired indole products irrespective of the stereochemistry of the precursors. Type I route seemed to be promising because we previously reported that the Cu‐catalyzed hydroarylation of 3‐( o ‐nitrophenyl)propiolates with arylboronic acids and subsequent Cadogan cyclization of the resultant 3,3‐diarylacrylate products afforded 3‐arylindole‐2‐carboxylates . However, the synthetic method for ( o ‐nitrophenyl)(trifluoromethyl)alkyne is strictly limited, even though various efficient methods have been developed for the synthesis of (trifluoromethyl)alkynes .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the development of a Mo‐catalyzed method enabled to perform the Cadogan cyclization at a lower reaction temperature . We previously synthesized 3‐arylindole‐2‐carboxylates under modified Cadogan conditions using P( n Bu) 3 or the molybdenum catalyst with PPh 3 ; the latter conditions gave better yields . Therefore, the Mo‐catalyzed Cadogan cyclization was applied to the trifluoromethyl‐substituted hydroarylation products.…”
Section: Methodsmentioning
confidence: 99%
“…This could then be oxidized to its fully aromatic counterpart, namely carbazole 31 (88%), upon exposure to 10% Pd on C in diphenyl ether at 210 °C (various attempts to effect the conversion 29 → 31 in a direct manner, or at least in a onepot-process, have been unsuccessful to date). Upon exposure of compound 31 to 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) it was oxidized, in 66% yield, to the natural product clauszoline K (32). On the other hand, treatment of compound 31 with BBr 3 effected cleavage of the associated ether residue and, thereby, the formation of the anticipated phenolic product 33 (84%).…”
Section: Carbazolesmentioning
confidence: 99%
“…Since this last compound has previously been converted into kopsihainanine A, the illustrated synthetic sequence constitutes a formal total synthesis of the racemic modification of this alkaloid. While the majority of the title cross-coupling reactions we have studied to date are of the general form shown in Scheme 17, their utility is considerable because of the differing modes of reductive cyclization 12,31,32 that can be applied to the products 85. Thus, as demonstrated in the multitude of settings presented above, when such products incorporate a nitro group, cyclizations using dihydrogen in the presence of various catalysts provide a range of indoles of the general form 86.…”
Section: Formal Total Synthesis Of the Cage-like Alkaloid Kopsihainan...mentioning
confidence: 99%